Experiential Marketing pada Produk Fashion Wanita - Nisa Lathifah; Gracia Frakcisa Stephanie Oentoe (Universitas Informatika dan Bisnis Indonesia, 2024)
This study examines the application of experiential marketing modules (SEMs) strategies on buste houder products at Wacoal Transtudio Mall Bandung. This study aims to determine the application of the five experiential marketing modules (SEMs) strategies according to Schmitt (1999), which consist of sense, feel, think, act, and relate in providing education by SPG Wacoal Transtudio Mall Bandung. This research uses a qualitative method with a case study approach. Data collection techniques used are interviews, observation, and documentation. The results of this study are the application of the five modules of the Experiential Marketing Modules (SEMs) Strategy, namely sense in vision, Wacoal consumers will see various forms of buste houder product models and see information about the dangers of gravity effect delivered verbally by SPG Wacoal this is also an auditory aspect. In the feel aspect, Wacoal consumers feel happy and feel helped by providing information about the gravity effect and SADARI and taking measurements so that consumers get products that suit their needs (act, think, and relate).